STUDY OF THE MOOMIYO-CONTAINING ORAL GEL EFFECT ON THE ACTIVITY OF THE ANTIOXIDANT DEFENSE SYSTEM IN EXPERIMENTAL PERIODONTITIS - Novytska, I.K.; Drum, M.B.; Nikolaeva, A.V.; Schnaider, S.A.; Tretyakova, O.V. (World of Medicine and Biology, 2020)
One of the important links in the study of pathogenesis indices in chronic generalized periodontitis is the intensity of lipid peroxidation and protective antioxidant systems that ensure a balance between the formation and metabolism of reactive oxygen species in cells. The purpose of our work was an experimental study of the oral cavity moomiyo-containing gel’s periodontal protection properties in the toxic calcium-deficient model. In order to simulate the pathology of periodontal disease, the laboratory white rats were given an EDTA solution (2 %) daily with drinking water, and three times a week the “Warfarin Orion” drug within 30 days. In total, 4 groups of animals were formed: group 1 – intact; group 2 – model reproduction; group 3 – model reproduction and application of “Placebo” gel to the mucous membrane of the alveolar process; group 4 – reproduction of the model and application of the moomiyo-containing gel to the mucous membrane of the alveolar process. Periodontal protective efficacy of the oral moomiyo-containing gel was shown against the background of a toxic calcium-deficient state: preservation (restoration) of protective antioxidant systems and inhibition of lipid peroxidation processes in the blood serum at the systemic level.
Keywords: lipid peroxidation; antioxidant protection; experiment; periodontitis; oral gel